Determination of Escherichia coli RNA Polymerase Structure by Single Particle Cryoelectron Microscopy - Ray, Pampa; Klaholz, Bruno P; Finn, Robert D; Orlova, Elena V; Burrows, Patricia C; Gowen, Brent; Buck, Martin; Heel, Marin van (Methods in Enzymology, 2003)
This chapter reviews the single particle cryoelectron microscopy that allows the determination of the structure of a bacterial mesophile RNAP. When compared with the crystal structures of RNAP from bacterial thermophiles, the medium-resolution electron density map highlights the features that are unique to the E. Coli enzyme and allows the localization of domains, that otherwise appear disordered in crystal structures of bacterial RNAP. Promoter specificity of RNAP is conferred by the additional sigma factor in the RNAP holoenzyme. Comparison of the different functional states of RNAP in E. coli has proved valuable in examining the structural basis of the transcription cycle. Single particle cryo-EM studies are extended to encompass the interaction of RNA polymerase with transcription factors in ternary complexes. The technique allows the study of different complexes in different functional states without the necessity to grow crystals first. Atomic fittings and homology modeling based on cryo-EM structural studies can be used to ascertain the functional role of such transcription complexes.